EMPTY THE MUSEUM, DECOLONIZE THE CURRICULUM, OPEN THEORY - Mirzoeff, Nicholas (The Nordic Journal of Aesthetics, 2017)
This essay reviews the possibility of the space of appearance under the authoritarian nationalism that has been ushered in by Brexit and the election of Donald Trump. For those working in and around higher education, I propose that the tasks with which we should begin are: decolonizing the curriculum; emptying the museum; and opening theory. Each of these categories has both a history in past resistance and liberation movements and a present-day dynamic that is explored here from the South African Rhodes Must Fall movement via Occupy Wall Street to the Free University and Antiuniversity.